SPATIAL ANALYSIS OF TSUNAMI EMERGENCY ASSEMBLY POINTS POINTS - Latif Muhammad Latif (Fakultas Pertanian, 2026)
Pondok Besi Subdistrict, Bengkulu City, is one of the areas that has a high level of vulnerability to tectonic earthquakes and tsunamis because it is located in the subduction zone where the Indo-Australian and Eurasian Plates meet. This study aims to analyze the feasibility of a tsunami emergency assembly point as part of a spatial-based disaster mitigation system. The research method used is a qualitative descriptive approach with spatial analysis. Analysis parameters include the distance of the assembly point to the coastline, evacuation travel time based on the road network, and land cover elevation. Data was obtained through field observations, spatial measurements. The results of the analysis showed that the emergency gathering point for the Tsunami disaster was at Sd 04, Pondok Besi subdistrict, Bengkulu City. KEYWORDS : tsunami, spatial analysis, disaster mitigation